Analytical solution of Marangoni convection flow of ethylene glycol-based nanofluid with heat transfer analysis - Rehman, Ali; İnç, Mustafa; Jawo, Edrisa; Sudarmozhi, K. (Elsevier B.V., 2025)
In microelectronics, aerospace, and chemical processing industries, advanced thermal management requires specialized techniques for heat and mass transfer at interfaces to optimize and ensure the reliability of the system. The focus of this study revolves around the MHD MC of ethylene glycol-based nanofluids (SiO2 and TiO2) for the first time in the literature. The aim is to assess the flow and heat transfer characteristics over a bidirectionally stretching surface with respect to the combined effects of the Marangoni parameter, volume fraction of the nanoparticle, Grashof number, Prandtl number, and Eckert number. The nonlinear governing PDEs of the flow are simplified with the use of a similarity transformation and converted to ODEs, which are then solved analytically with the HAM. Various velocity and temperature fields are computed, and the skin friction and NN are parametrically explained. Regarding the magnetic parameter, the dominant flow and boundary velocity are suppressed by 30%, while surface heat transfer increases by 20% with a higher nanoparticle volume fraction. Also, more convective flow is achieved with a rise in the Marangoni and Grashof numbers, and the highest NN is recorded with specific physical parameter combinations. The developed framework, along with the results, provides evidence of the vital role that interaction effects play within the scope of MFs and nanoparticle-enhanced fluids, as well as in the potential development of more advanced and effective nanofluid-based cooling and thermal control systems. In relation to specific engineering fields and disciplines, the results hold significance for cooling microelectronics, thermal management in the aerospace industry, and more refined heat exchangers in the chemical industry. © 2025 The Authors
Keywords: HAM; Magnetohydrodynamics; Marangoni convection (MC); Mathematica software; Nanofluid